2008
DOI: 10.1111/j.1399-5618.2008.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of patients with bipolar disorder commenced on lithium prophylaxis during hospitalization: a complete 15‐year register‐based follow‐up

Abstract: The overall outcome in patients beginning prophylactic treatment is unsatisfactory. However, due to the observational design and the lack of detailed treatment information during the long follow-up period, inferences about the efficacy of lithium cannot be made from this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…People who attempt suicide once are more likely to die from all other causes of death in the next 5 years in comparison with the rest of the population 16, 17. Different studies have reported somewhat different findings, with death rates ranging from 4% to 15% 5 to 15 years after a suicide attempt 16, 18, 19. This is actually similar to the overall 5‐year patient survival rate after LT.…”
Section: Discussionsupporting
confidence: 52%
“…People who attempt suicide once are more likely to die from all other causes of death in the next 5 years in comparison with the rest of the population 16, 17. Different studies have reported somewhat different findings, with death rates ranging from 4% to 15% 5 to 15 years after a suicide attempt 16, 18, 19. This is actually similar to the overall 5‐year patient survival rate after LT.…”
Section: Discussionsupporting
confidence: 52%
“…-the question raised in an editorial [41] , can now be answered conclusively: yes, it does, if the treatment is applied and monitored in a rational, careful and individualized way. While there are rare negative findings in this respect [42] , they can most likely be explained by incomplete patient follow-up and insufficient information on patients' compliance with lithium. This saving of lives considerably adds to the preference of lithium when the cost-effectiveness of treatment with various mood stabilizers is assessed [43] .…”
Section: Resultsmentioning
confidence: 94%
“…Despite the widespread clinical belief that antidepressants may trigger bipolar symptoms in susceptible individuals, empirical evidence for this is lacking (19). However, addition of a mood stabilizer after response to antidepressant treatment may be beneficial in those who manifest sub-threshold bipolarity (38). …”
Section: Discussionmentioning
confidence: 99%